Estimating study sample size and assessing reiability of peak fat oxidation (PFO) data (g/min) collected during fatmax tests, with consideration for menstrual cycle in endurance-trained women - Molloy, E.; Murphy-Griffin, M.; Harrison, M. (European Journal of Physical Education and Sport Science, 2025)
Background: Sample size estimations are completed to determine the number of participants needed to highlight a relevant treatment effect [1]. This is crucial to ensure that the results are reliable. Estimating sample size can also assist researchers by informing the financial outlay for a project and minimising any over spend.